Estimation of the aggregate import demand function for Mexico: a cointegration analysis - Romero Tellaeche, José Antonio (2023)
Purpose: This study estimated total import demand elasticities concerning income, import prices and domestic prices. A high propensity to import constitutes a significant obstacle to economic growth in Mexico since the benefits of increased exports or any other aggregate demand expansion leak to the rest of the world. Design/methodology/approach: This paper estimated a Vector Error Correction Model of the total import demand elasticities concerning income, import prices and domestic prices. Total imports are a dependent variable, while Gross Domestic Product (GDP) and import and domestic prices are the independent variables. Findings: The principal finding is that an increase of 1 peso in the Mexican GDP leads to a rise of 0.50 pesos in Mexican imports; the elasticity of import demand for prices is low. Still, the elasticity of import demand for domestic prices is 2.14 times greater than that for import prices. These results have significant economic policy implications, such as promoting the expansion of the domestic market and the national content of exports. Research limitations/implications: It is tempting to estimate the import demand function for the entire 1993–2019 period since such data is available. But by doing so, the authors would overestimate the propensity to import, given that from 1993 to 2019, the proportion of imports as a percentage of GDP went from 11.37 in 1993 to 29.66 in 2019. Therefore, it makes more sense to estimate the import demand function from 2000 to 2019, a period with a stable proportion of imports to GDP. Originality/value: A high level of imports in developing countries means that much of their aggregate demand is filtered abroad. Therefore, the low impact of its exports on GDP is related to the Mexican economy’s high imports. The authors calculate this relationship with new data and methods.